Existência e multiplicidade de soluções para uma classe de sistemas elípticos em Rn - Silva, Wendel Leite da (2016)
In this work, we study questions related to the existence, multiplicity and asymptotic behavior with respect to a positive parameter of nonzero solutions for a class of coupled semilinear elliptic systems in RN, where the potentials are not negative and not necessarily coercive. To obtain the results, we use variational methods, namely, minimax type theorems involving the Palais-Smale and strong Cerami conditions.